SCADA For Substation with GSM PIC16f877A - Muntode, Ashish Bagate; Muntode, Akshay Khichade; Muntode, Aniket Borkar; Muntode, Nikhil More; Muntode, Patole S. S. (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Electricity is the most important resource that we have in our daily routine. Can we even imagine a day without electricity? From Internet surfing to domestic applications, from industrial usage to household usage, everywhere we need electricity. So, what about its optimal use? Being a useful resource, it is our responsibility that we use electricity with proper care and with zero wastage. Hence load shedding option is one of the approaches that we can go with. This can help us to save electricity up to a large extent. The demand for electrical energy is increasing. Today over 21% of the total electrical energy generated in India is lost in transmission (4-6% ) and distribution (15-18%). The electrical power deficit is currently about 18% in the country. Clearly, reduction in distribution losses can reduce this deficit by significantly. Its possibility to bring down the distribution losses to a 6-8 % level in India with the help of newer technological option (including information technology) in the electrical power distribution sector which will enable better monitoring and control.